Efektifitas Aturan Main Untuk Game Edukasi Kosakata Bahasa Arab Berbasis Mobile - Sani, Dian; Herumurti, Darlis; Kuswardayan, Imam (Fakultas Teknologi Informasi Institut Teknologi Adhi Tama Surabaya, 2017)
The game is ways to remove saturation from various kinds of affairs. The game also used as learning media. This educational game is usually used to invite users to play while learning. Languages and games must be complementary. Because of the language is important, it needs an effective and efficient way to increase interest in language learning. So the focus of this research is to create three mobile gaming applications with educational content of Arabic vocabulary which gameplay are different and analyze which applications are effective for users in recognizing Arabic vocabulary. Testing is done to find out if the application is effective for players to know and learn Arabic language. Samples taken are second grade students Madrasah Ibtidaiyyah who know the hijaiyah letters. Pre-test, treatment and post-test are part of the testing phase. Test results were analyzed using ANOVA one way method. The results of this study indicate that there is an increase in learning ability of participants through the medium of Arabic educational games with a value of 3.65 beyond the critical value with a significance level of 5% or 0.05 of 3.10. When Hypothesis 0 is rejected, then the comparison test between groups (games) with Scheffe method with critical value 2.48. The result is a third game with a value of 2.57 is said to be effective than the first game (0.58) and the second (2.00). The second game (2.05) is said to be more effective than the first game (0.51).Keywords: Educational Game, Game Effectiveness, Mobile games, Arabic vocabulary, ANOVA.